The Implementation of Constructivism Learning Models to Improve The Comprehending of Physics Concepts on Vibration And Wave Materials on Students of Seventh Grade At Second Semester in MTSN 2 Wolowaru - Kuran Mbadhi; Melkyanus B.U. Kaleka; An Nisaa Al Mumin Liu (Journal of Science Education Research, 2020)
The problem statement of the research was: does the implementation of the constructivism learning model improve the comprehending of physics concepts in thevibration and wave material of students in seventh-grade of MTS Negeri Wolowaru? The research aimed to determine the implementation of the constructivism learning model in improving the comprehending of the physics concept in the vibration and wave material of students in seventh-grade of MTS Negeri Wolowaru. The research used a quantitative approach. The population of the study was 60 students of seventh-grade of MTS Negeri Wolowaru. Meanwhile, the sample was 20 students selected through a random samplingtechnique. The data were the test results of the vibration and wave material. Data analysis was performed by the t-test. Based on data analysis and discussion, it concluded that the implementation of the constructivism learning model improved the students' comprehending of physics concepts on vibration and wave material. This conclusion was proved by the results of data analysis, namely tcalculate greater than ttable= 4.395 greater than 1.729 at the significant level = 0.05 and dk = 19